2021
DOI: 10.1002/cam4.3786
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of cytogenetic and molecular genetic abnormalities in 634 Chinese patients with myelodysplastic syndromes

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In total, there are 5 studies indicating that SRSF2 mutation cause higher risk of AML transformation. Meanwhile, the studies by Hong et al and Yan et al did not find any association between SRSF2 and AML transformation (Hong et al, 2015;Yan et al, 2021). Pooled hazard ratio showed that patients with SRSF2 mutation had higher risk of leukemia transformation (HR 2.62; 95% CI: 1.54-4.45; p= .0004).…”
Section: Pooled Analysis Of Splicing Factors Gene Mutationsmentioning
confidence: 98%
See 1 more Smart Citation
“…In total, there are 5 studies indicating that SRSF2 mutation cause higher risk of AML transformation. Meanwhile, the studies by Hong et al and Yan et al did not find any association between SRSF2 and AML transformation (Hong et al, 2015;Yan et al, 2021). Pooled hazard ratio showed that patients with SRSF2 mutation had higher risk of leukemia transformation (HR 2.62; 95% CI: 1.54-4.45; p= .0004).…”
Section: Pooled Analysis Of Splicing Factors Gene Mutationsmentioning
confidence: 98%
“…However, 4 articles were not in English language, 2 articles were nonhuman studies, 6 articles did not have outcome of AML progression, and 6 articles did not have adequate data for hazard ratio calculation. Thus, we identified 14 articles to be used for this systematic review and meta-analysis (Dicker et al, 2010;Malcovati et al, 2011;Walter et al, 2011;Thol et al, 2012;Wu et al, 2013a;Lin et al, 2014;Hong et al, 2015;Kang et al, 2015;Jung et al, 2016;Tefferi et al, 2017;Xu et al, 2017;Gangat et al, 2018;Lin et al, 2018;Yan et al, 2021).…”
Section: Study Selectionmentioning
confidence: 99%
“…In recent years, the development of new technologies has led to a great improvement in our knowledge of the genetic landscape in MDS. Multiple studies have investigated the role of somatic mutation in MDS patient outcome (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%